Pediatric evidence-based imaging guidelines for adult trauma providers significantly reduces radiation exposure to children. (January 2023) - Wu, Anna; Edwards, Mary J; Le, Rachel; Ata, Ashar; Adderly, Jasmine; Savage, Colleen; Rosati, Carl; Edwards, Kurt; Duncan, Luke
Introduction: Evidence suggests that stand-alone pediatric trauma centers outperform adult and combined adult/pediatric trauma centers in limiting radiation exposure to injured children. We sought to determine the impact of implementing evidence-based guidelines for pediatric imaging at a combined adult (level 1) and pediatric (level 2) center. The initiative focused on trauma/critical care surgeons as the pediatric surgeons did not participate in the resuscitation and initial evaluation of injured children. Methods: Imaging guidelines were developed from existing clinical studies. After 3 months of education, guidelines were implemented, and regular feedback was given to providers regarding compliance. Data were collected from the trauma registry for all pediatric patients (aged less than 15 years), in calendar years 2017 (pre-guideline) and 2019 (post-guideline). All admissions were analyzed, with subgroup analysis of children with multisystem trauma admitted to the trauma surgery service. Results: Following guideline implementation, mean computed tomography (CT) scans per injured child fell by over 50% (.93 vs .45). For patients admitted to the trauma service, the mean fell by 58% (1.82 vs 0.76). The number of patients receiving more than 1 CT significantly decreased for all children (26% vs 10%), and particularly those admitted to the trauma service (52% vs 17%). During this time, there was only one injury missed at the initial admission, which was clinically insignificant (non-displaced skull fracture). Conclusions: Implementation of evidence-based guidelines for imaging eliminates disparity in practices between a combined adult/pediatric trauma center and stand-alone pediatric trauma centers.